Corporate governance and firm performance in an emerging market: the case of Malaysian firms - Haron, Razali; Abdullah Othman, Anwar Hasan; Nomran, Naji; Md Husin, Maizaitulaidawati (IGI Global, 2020)
This study examines the corporate governance mechanisms and how they affect firm performance in Malaysia. After the financial crisis in 1997/98, the CG issues have been the most debated, discussed, and researched in the attempt to improve the CG structure accommodating every economy regardless of the economic landscapes. Using a rich and huge data on Malaysian firms for 16 observation years, this study found that the MCCG has been of a closely referred blueprint by firms in Malaysia to improve firms’ performance. Certain CG mechanisms do have significant impact on firm performance. Firms seem to operate in a large board size indicating a positive relationship with performance and board independence. CEO duality is negatively related, in support of separation of roles, complementing the result of board independence and ownership structure as positively related to performance. Agency theory seems to be the dominant theory influencing the CG structure of firms in Malaysia.